The Impact of Energy Consumption Revolution on Farmers' Happiness: An Empirical Analysis From China - Zhiyao Xu; Rong Ge (Frontiers Media S.A., 2022)
This study divided the impact of energy consumption revolution on farmers' happiness into direct and indirect effects. We empirically tested these effects using the Chinese General Social Survey (CGSS) household data in 2015 and the mediation-moderation model. The results showed that: (1) The rural energy consumption revolution has increased the probability of farmers' happiness level by 22.7%. The direct effects with obvious marginal decrement accounted for the main part (over 90%) of the total effect, but the multi-dimensional mediating mechanism was not yet robust. (2) The revolution of rural energy consumption has slightly improved farmers' happiness through the mediating role of increased leisure activities, while the negative impact of increased use-cost on the happiness of low-income farmers was nearly significant. (3) Regional economy, household income, and energy type played negative roles when moderating the above process. To low-income households in the less-developed western region, the total effects were more evident in the aspect of electricity use. Hence, several policy recommendations have been further made, including inclusive energy and strategic synergies.